Synthesis of peptides via cobalt (III) chelates of amino acid methyl esters : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Chemistry at Massey University - Knighton, Derek Robin (Massey University, 1979)
PEPTIDE SYNTHESIS – THE NEED FOR FURTHER METHODS The rapid development of the field of peptide synthesis provides an ever increasing number of techniques available to the peptide chemist (1, 2, 11). Each technique which has been developed is subject to particular advantages and disadvantages. For example, one of the most widely used methods, solid phase peptide synthesis (3) has several associated problems. Uiese are: diketopiperazine formation (4, 5), lability of the ester linkage to the solid phase (6), slower coupling reactions compared with solution phase syntheses (12), the occurrence of deletion peptides which are difficult to separate from the product (7), chain termination caused by steric hindrance from the resin (8) or the conformation of the peptide (9) and the side reactions which occur during the addition of glutamine and asparagine residues when N,N'-dicyclohexylcarbodiimide (DCC) is used as the coupling reagent (10). Since no one technique has overcome all of the problems associated with peptide synthesis there is a need for continued research in this area. The number of amino acids and their diverse properties results in an enormous variety of possible synthetic peptides. With a large variety of techniques at his disposal the peptide chemist is better equipped to solve particular problems associated with the synthesis of these peptides. This thesis describes the effective use of one more synthesis technique. THE STRATEGY USED IN PEPTIDE SYNTHESIS Current methods of peptide synthesis involve the sequential addition of amino acids from the carboxy to the amino terminal. To ensure only the amino group of the growing peptide chain, N₂-Peptide, is available for reaction, the amino group on the amino acid must first be protected (with group X). The carbonyl on the amino acid is then activated (with group Y) and the protected and activated amino acid is added to the growing peptide chain resulting in a specific condensation reaction. The amino protection is removed and the peptide is then free to be used in another cycle as shown in Figure 1.1.[FROM INTRODUCTION]
Keywords: Lipoproteins; Peptide synthesis